2010
DOI: 10.1111/j.1751-1097.2009.00632.x
|View full text |Cite
|
Sign up to set email alerts
|

Optical and X‐ray Fluorescence Spectroscopy Studies of Bone and Teeth in Newborn Rats After Maternal Treatment with Indinavir

Abstract: An experiment estimating influence of antiviral drug indinavir treatment during pregnancy on bones and teeth development in newborn rats was performed. Two different fluorescence noninvasive spectroscopy techniques, i.e. laser (407 nm)-induced fluorescence method to characterize the organic fluorescent molecules and X-ray fluorescence analysis to determine mineral components were used to study the surface response of femur, mandible and incisor during their formation in the first month of a rat's life. Differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 51 publications
(73 reference statements)
2
9
0
Order By: Relevance
“…Our studies of newborn rat bones influenced by antiretroviral drugs—indinavir and zidovudine administered to pregnant rat females indicated disturbed concentration of calcium and zinc, which was partly published in Ref. . Strontium and iron content were also affected by administration of these drugs, what can be seen in Fig.…”
Section: Discussionsupporting
confidence: 54%
“…Our studies of newborn rat bones influenced by antiretroviral drugs—indinavir and zidovudine administered to pregnant rat females indicated disturbed concentration of calcium and zinc, which was partly published in Ref. . Strontium and iron content were also affected by administration of these drugs, what can be seen in Fig.…”
Section: Discussionsupporting
confidence: 54%
“…Many efforts have been made to optimize the detection and imaging of diseased tissues, exploring the diagnostic potential of exogenous fluorophores developed for photodynamic diagnosis and therapy [8]. Fluorescence spectroscopy may also give valuable information in non-cancerous cases, for example, fluorescence spectroscopy was applied as a tool for bone development monitoring in new-born rats [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge of the status of the above characteristics of an organism helps ensure early detection of subclinical pathologies, including early detection of premalignant and neoplastic changes [10,[15][16][17][18][19][20] and differential diagnosis of different types of pathological changes [9,19]. It can also be used to assess the impact of drugs on tissues [21,22], distinguish between healthy body tissues and dysplastic lesions [19], evaluate tumour lesion demarcation [19,23,24] and provide early detection of initial caries in teeth [12,[24][25][26][27]. Apart from its possible application in diagnostics, fluorescence also serves as an important guide in longterm evaluations and monitoring of spontaneous or treatment-induced changes in tissues, including as a method for monitoring the carious spot in teeth and its remineralisation [12,13,[24][25][26][27][28][29][30][31], monitoring the effects of antibiotic therapy and phototherapy in bacteriological skin diseases [13], as well as in photodynamic treatment (PDT) of neoplasms [28] and precancerous conditions [20,29].…”
Section: Discussionmentioning
confidence: 99%
“…Zidovudine stimulates RANKL -dependent osteoclastogenesis by expression of TRAP (tartare-resistant acid phosphatase promoter), and thus increases osteoclast activity and bone density loss (BMD) [32]. By analysing skeletal development in rats Drzazga et al have demonstrated a significantly lower concentration of calcium in the mandible in 7 and 28-day-old animals treated with indinavir compared to the control group [22]. According to Emami, et al [33], the loss of tooth mineral manifests itself in a decrease in fluorescence intensity, whereas Angmar -Mansson observed that 0.15kg.m mineral loss reduces the maximum fluorescence emission by 10% [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation